2014
DOI: 10.1155/2014/817283
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early-Stage Pressure Ulcers by Using Autologous Adipose Tissue Grafts

Abstract: Assessing pressure ulcers (PUs) in early stages allows patients to receive safer treatment. Up to now, in addition to clinical evaluation, ultrasonography seems to be the most suitable technique to achieve this goal. Several treatments are applied to prevent ulcer progression but none of them is totally effective. Furthermore, the in-depth knowledge of fat regenerative properties has led to a wide use of it. With this study the authors aim at introducing a new approach to cure and prevent the worsening of earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…11,18 The survival of grafted fat over time is a key issue. For ischial and sacral lipofilling, Marangi et al 13 showed significant improvement of subcutaneous thickness at 3 months follow-up in all but one of their 42 patients. For breast lipofilling, it seems that most of the volume loss occurs within the first 3 months after surgery, 11,12 and that the graft is steadily integrated at the 9th month so that further resorption thereafter is unexpected.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…11,18 The survival of grafted fat over time is a key issue. For ischial and sacral lipofilling, Marangi et al 13 showed significant improvement of subcutaneous thickness at 3 months follow-up in all but one of their 42 patients. For breast lipofilling, it seems that most of the volume loss occurs within the first 3 months after surgery, 11,12 and that the graft is steadily integrated at the 9th month so that further resorption thereafter is unexpected.…”
Section: Discussionmentioning
confidence: 91%
“…Our results confirm the good outcomes already described for ischial and sacral lipofilling in the treatment of earlystage pressure ulcer in chronic bedridden patients with neurologic conditions, including patients with SCI. 13 With the advent of liposuction technique in the 1980s, plastic surgeons obtained access to large volumes of adipose tissue. In the 1990s, Coleman described a three staged procedure for fat grafting consisting of: (1) manual lipoaspiration under low pressure; (2) 3 min of centrifugation at 3400 r.p.m.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Autologous lipofilling has become popular in aesthetic and plastic surgery for many indications, including scar remodeling (especially in acne and burn patients), lip augmentation and deformity treatment, mandibular and buccal deficiency of both bone and soft tissue after tumor resection management, skin rejuvenation, wrinkle filling, lipo-facelift, malar and mental regions augmentation, 7 and breast reconstruction after cancer or for deformities. 8 This technique has found application also in vocal cord tissue regeneration, 9 in the treatment of chronic ulceration, 10 end-stage radiation dermatitis, 11 alopecia, 12 and other medical applications. Stem cell therapy has shown to be promising in aesthetic and reconstructive surgery 13 and several recent studies have shown adipose tissue as a convenient source of multipotent adult stem cells, called adipose-derived stem cells (ASCs).…”
mentioning
confidence: 99%